2005
DOI: 10.1016/j.femsle.2004.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas hydrophilaclinical and environmental ecotypes as revealed by genetic diversity and virulence genes

Abstract: Aeromonas hydrophila strains recovered from clinical samples and ambient sources were phenotypically and genetically identified. In addition, the distribution of putative virulence factors was assayed. To determine the genetic diversity of these strains, random amplification of polymorphic DNA (RAPD) and enterobacterial repetitive intergenic consensus (ERIC)-PCR markers were used. The discriminatory ability of the techniques, using Simpson's index, was 0.96 for both methods. The most consistent dendrogram was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 58 publications
9
52
3
2
Order By: Relevance
“…In the present study, irrespective of the Aeromonas species, we found that the T3SS genes were more prevalent in water isolates (for aexU, 68 of 146 isolates were positive; for ascV, 60 of 146 isolates were positive) than in clinical isolates (for aexU, 5 of 53 isolates were positive; for ascV, 5 of 53 isolates were positive), a finding in agreement with data obtained in another recent study (4). However, these genes were more prevalent in clinical isolates than in water isolates specifically for the A. hydrophila group (Table 6).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, irrespective of the Aeromonas species, we found that the T3SS genes were more prevalent in water isolates (for aexU, 68 of 146 isolates were positive; for ascV, 60 of 146 isolates were positive) than in clinical isolates (for aexU, 5 of 53 isolates were positive; for ascV, 5 of 53 isolates were positive), a finding in agreement with data obtained in another recent study (4). However, these genes were more prevalent in clinical isolates than in water isolates specifically for the A. hydrophila group (Table 6).…”
Section: Discussionsupporting
confidence: 93%
“…A search of GenBank for the ast gene sequence using the BLAST N system showed a 96% homology with the ast gene in the complete genome of A. hydrophila (Tables 1 and 3). These results are in agreement with earlier studies (2,21,25) and may suggest or confirm that the ast gene might be specific for A. hydrophila HG1 and might represent a potential taxonomic tool for the identification of A. hydrophila HG1. The low prevalence (2%) of the ast gene in food-borne Aeromonas isolates in the present study is similar to that reported in earlier studies involving human cases of diarrhea in India (23) but contrasts with the reported high prevalence of the ast gene in waterborne isolates (30%) from the United States (22), in isolates from healthy (48%) and sick (71%) children and in environment isolates (66%) from Bangladesh (3), and in clinical human isolates (13%) from southern Taiwan (25).…”
Section: Salmonicidasupporting
confidence: 93%
“…Although this gene occurs widely in clinical (2,3,23) and in environmental isolates of Aeromonas spp. (2,21), the data on the presence of the ast gene in food-borne isolates of Aeromonas spp. are lacking.…”
Section: Salmonicidamentioning
confidence: 99%
“…This diversity indicates the need for regular monitoring of Aeromonas strains for pathogenic characteristics and for the possibility of epidemic strains that could be circulating in the population. Studies of clinical and environmental ecotypes of Aeromonas in Mexico demonstrated the high intraspecific diversity within A. hydrophila and revealed a clear differentiation of strains according to their ecological origins (16). The same study also confirmed, based on the distribution of virulence-related genes, that A. hydrophila is a genetically-heterogeneous species that harbour ecotypes which have different pathogenic potentials to humans and other animals.…”
Section: Discussionsupporting
confidence: 52%